An investigation into preservation of wood from Venice foundations. (15th May 2016) - Macchioni, Nicola; Pizzo, Benedetto; Capretti, Chiara
Highlights: Description of a methodology to sample wood from Venice foundations. Analyses to describe wood species constituting piles of Venice foundations. First results about the state of preservation of wood from Venice foundations. Abstract: The present paper deals with wood from Venice historic centre foundation elements. Samples were taken from both piles and planking (horizontal elements positioned above the pile heads), in 5 out of 6 districts of Venice. Considering the watery milieu, the diagnostic methodology for waterlogged archaeological wood was adopted, performing anatomical, chemical and physical characterisations. Our results show that the wood used for Venetian foundation elements belong to a small group of 5–6 species (alder, larch, oak, pine, elm and spruce, although the latter was probably of more recent introduction). Most of the analysed samples evidenced decay, which in some cases was high (residual basic densities of only 32%, and values of the ratio holocellulose to lignin as low as 0.3). It was evidenced how the state of preservation of wood was related to several factors, including: thickness of the element, depth of burial, horizontal/vertical position, and wood species. It was also shown how ash content does not reflect the state of preservation of waterlogged material, as it is sometimes reported in the literature. The diffuse decay was apparently not related to the general stability of the buildings under study.